Fabrication of air-hybrid all terrain vehicles front suspension system - Leong, Guo Bang (2013)
This thesis is about fabricating of Hybrid-air ATV front suspension system.It consists of spring shock absorber and linkage to support the vehicles. Suspension system plays an important role in vehicles.It is to ensure the safety and riding comfort of the passengers during their journey. It is also providing sufficient damping force to overcome the damping of vehicle due to the road condition.The process of fabricating the suspension system is one of the crucial part which will affect the quality and function of the suspension system. The suspension system used for the Air-hybrid ATV suspension system is double wishbone suspension system.The reverse engineering is done to design and fabricate the suspension system.The project is to fabricate the part based of the design given. Most of the part of the suspension system is design to fit the chassis of the Air-hybrid ATV. Thus, the part must follow exactly the dimension of the drawing else they could not fit each other. Part of the suspension system also need to be fitted to the part brought from market and the chassis of the Air-hybrid ATV chassis. Thus, the design refinements are needed to ensure that all the parts of the suspensions system can integrate to each part. It is impossible to fabricate the product as same as the engineering drawing. Therefore, by refining the design, the product can be done as close as the design given.Material preparation and methods chosen for fabricating the part of suspension system will also decide the quality and functionality of the suspension system.Fabricating suspension system of the Air-hybrid ATV suspension system is not easy, but by doing well progress planning and using the right method, the suspension system could be fabricated as close as the design to ensure the quality of the suspension system.